ANALISIS PERAN STRATEGI INOVASI, MANAJEMEN OPERASIONAL DAN STRATEGI PROMOSI DALAM MENINGKATKAN DAYA SAING UMKM AYAM GEPREK KEN DI UNIVERSITAS MALAHAYATI - Elianjaya, Anggi (DINAMIKA (Jurnal Manajemen Akutansi Bisnis dan Kewirausahaan), 2025)
This study aims to analyze the influence of product innovation, operational management, and promotion strategy on the competitiveness of the UMKM (Micro, Small, and Medium Enterprises) Ayam Geprek Ken at Universitas Malahayati. The study employs a qualitative descriptive approach using in-depth interviews, field observation, and documentation as data collection techniques. The results show that limited product innovation, unstable raw material supply, suboptimal service, and underdeveloped promotional strategies significantly reduce customer satisfaction and attractiveness. These findings emphasize the importance of continuous product development, efficient operations, and well-structured digital promotion to enhance the competitiveness of culinary MSMEs in an increasingly competitive market.